2022
DOI: 10.5530/pj.2022.14.103
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of total polyphenols and flavonoids, antioxidant activity, and Sinensetin and Imperatorin contents of Imperata cylindrica root ethanol extract

Abstract: Introduction: Imperata cylindrica, commonly known as cogon grass, is currently widely distributed and used as a medicinal plant. The major compounds that have been isolated and identified are polyphenols and flavonoids, which have many biological activities such as antioxidant, and anticancer. Polyphenols and flavonoids are mostly found in the roots and leaves. This study aimed to perform phytochemical screening on I. cylindrica root ethanol extract from Sragen, Central Java, Indonesia and determine the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…18 Previously, sinensetin and imperatorin were found in similar concentrations in a root ethanol extract of Imperata cylindrica. 19 Researchers have found that imperatorin combined with other drugs works better in vitro. The combination of quercetin (50-100 μM) and imperatorin (50-100 μM) was more effective in HeLa cells and Hep-2 cells than either drug alone.…”
Section: Discussionmentioning
confidence: 99%
“…18 Previously, sinensetin and imperatorin were found in similar concentrations in a root ethanol extract of Imperata cylindrica. 19 Researchers have found that imperatorin combined with other drugs works better in vitro. The combination of quercetin (50-100 μM) and imperatorin (50-100 μM) was more effective in HeLa cells and Hep-2 cells than either drug alone.…”
Section: Discussionmentioning
confidence: 99%
“…12,[18][19][20] The root of Cogon grass (Imperata cylindrica (L.)), is a common traditional medicine in Indonesia, 21 has been proven to have antioxidant and anti-inflammatory properties due to its polyphenols contents. [22][23][24][25] Previous study found pretreatment of mice with oral cogon grass root extract (CGRE) for two weeks, significantly reduced serum cholesterol levels after acute olive oil loading. 25 There is evidence polysaccharide from root of I. cylindrica can reduce cholesterol level, 26 and we want to know if it also has impact on LAB.…”
Section: Research Articlementioning
confidence: 99%
“…[22][23][24][25] Previous study found pretreatment of mice with oral cogon grass root extract (CGRE) for two weeks, significantly reduced serum cholesterol levels after acute olive oil loading. 25 There is evidence polysaccharide from root of I. cylindrica can reduce cholesterol level, 26 and we want to know if it also has impact on LAB. Thefore, the objective of this study is to explore whether the GCRE has prebiotic effects to stimulate LAB growth in mice intestine.…”
Section: Research Articlementioning
confidence: 99%